anonymous
  • anonymous
1/t-2 = t/8
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Is the -2 on the bottom?
anonymous
  • anonymous
The t-2 is all on the bottom
anonymous
  • anonymous
Whenever you have a fraction = fraction you can cross multiply. 1 * 8 = (t - 2) * t

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
8 = t^2 - 2t
anonymous
  • anonymous
0 = t^2 - 2t - 8 0 = (t - 4)(t + 2) t = 4 or t = -2
anonymous
  • anonymous
Thank You
anonymous
  • anonymous
What about when you add another number into the equation? 4/3(c+4) + 1 = 2c/(c+4)
anonymous
  • anonymous
Common denominator is 3(c + 4) so you put that on top of each term. 3(c+4)*4 3(c+4)*1 2c ------- + = ------- 3(c+4) c + 4
anonymous
  • anonymous
Oops I missed the last term 3(c+4)*2c -------- c+4
anonymous
  • anonymous
4 + 3c + 12 = 6c
anonymous
  • anonymous
3c + 16 = 6c
anonymous
  • anonymous
16 = 3c
anonymous
  • anonymous
16/3 = c c = 16/3 or 5 1/3
anonymous
  • anonymous
ok thank you 1 more
anonymous
  • anonymous
(a/a+3) = (2a/a-3) -1
anonymous
  • anonymous
Common denominator of (a + 3)(a - 3) so put that on top of every term
anonymous
  • anonymous
(a + 3)(a - 3)a (a + 3)(a - 3)*2a (a + 3)(a - 3)*1 ------------ = -------------- - -------------- (a + 3) (a - 3) Cancel the bottoms into the top
anonymous
  • anonymous
thank you so much for your help
anonymous
  • anonymous
(a - 3)a = (a + 3)2a - (a + 3)(a - 3) a^2 - 3a = 2a^2 + 6a - (a^2 - 9) a^2 - 3a = 2a^2 + 6a - a^2 + 9 distribute the - sign a^2 - 3a = a^2 + 6a + 9 add like terms -3a = 6a + 9 subtract a^2 from both sides -9a = 9 subtract 6a from both sides a = -1

Looking for something else?

Not the answer you are looking for? Search for more explanations.